Drivers for non-profits' success: Volunteer engagement and financial sustainability practices through the resource dependence theory - Sehrish Ilyas; Mattiullah Butt; Fouzia Ashfaq; Daniela Acquadro Maran (Economies, 2020)
The strategies that non-profit organizations choose for volunteer engagement and financial sustainability are of the utmost importance for successful work. The main purpose of this study was to investigate feasible strategies for volunteer engagement and financial sustainability. Interviews were conducted to obtain data on the experience of volunteer managers in dealing with volunteers and financial matters together. Qualitative data analysis methods were used to code and analyze the data. Significant themes emerged from the data gathered through interviews that highlighted the strategies for volunteer engagement and financial sustainability chosen by the managers of non-profit organizations. From the manager's perspective, the following strategies were considered important for engaging volunteers at non-profit organizations (NPOs): "building the skill sets of volunteers", "fulfilling ulterior motives", and "administering a culture of administrative support". Moreover, "local fundraising preference", "transparency", and "building trust" were regarded as successful strategies for maintaining financial sustainability. The findings of this study showed that, to function smoothly, non-profit organizations need to follow certain strategies to be cautious about volunteers as well as finance. The findings provide fruitful implications for practitioners and policy makers, and these are discussed in the paper. Furthermore, the limitations addressed in the study suggest a future direction for research in terms of study design and more focus on study informants.
Keywords: 330; financial sustainability; formal volunteering; managing non-profit organizations; non-profit organizations managing volunteers; thematic analysis; volunteer engagement retention